Γδ T lymphocytes in the peripheral blood of patients with tuberculosis with and without HIV co-infection. Issue 4 (1st April 2002) - Carvalho, A C C; Matteelli, A; Airò, P; Tedoldi, S; Casalini, C; Imberti, L; Cadeo, G P; Beltrame, A; Carosi, G
Abstract : Background: Several recent studies suggest that γδ T lymphocytes play an important role in immunity against Mycobacterium tuberculosis. However, the dynamics of these cells in the peripheral blood of patients with tuberculosis (TB) with and without HIV infection is not fully understood. A study was undertaken to evaluate the profile of the γδ T cell population in patients at the time the diagnosis of TB was established. Methods: A cross sectional study was performed in consecutive TB patients from the Department of Infectious Diseases, Spedali Civili, Brescia. CD4+, CD8+ and Vδ1 and Vδ2 T cell counts were analysed. Lymphocyte surface membrane expression was evaluated with the FITC-TCRγδ, -Vδ1, -Vδ2 and PE-Vδ1 monoclonal antibodies. Blood donors and HIV seropositive asymptomatic individuals acted as controls. Results: Seventy four TB patients were evaluated, 20 of whom (27%) were co-infected with HIV. HIV seronegative TB patients (n=54) had total γδ T cells and Vδ1 subsets comparable to those in blood donors (n=39). However, the percentage with the Vδ2 subset was significantly lower in patients with TB than in controls (median 1.5 v 2.1; p=0.05). Responsiveness to PPD was not associated with predominance of a specific γδ T cell subset. HIV seropositive individuals had a decreased percentage of circulating Vδ2 cells at a level similar to that in HIV seronegative TB patients, regardless of the presence of active TB. Conclusions: HIV seronegative TB patients and HIV infected individuals (with or without active TB) have a reduced number of circulating Vδ2 T cells compared with healthy individuals. Whether TB and HIV infection share a common mechanism causing Vδ2 T cell depletion still needs to be established.